THE EFFECT OF ANEMIA ON THE INCIDENCE OF PREMATURE RUPTURE OF MEMBRANE (PROM) IN KERTHA USADA HOSPITAL, SINGARAJA, BALI - Putu Irma Pratiwi; Ova Emilia; Farida Kartini (Belitung Raya Foundation, Indonesia, 2018)
Background: Premature Rupture of Membranes (PROM) causes morbidity and mortality complications in both maternal and perinatal. Pregnancy with anemia where low hemoglobin level which is less than 11.1 g / dL can be the cause of PROM through biological mechanisms and mechanisms of disease. Objective: This study aims to compare the risk of PROM between anemic maternal mothers and non-anemic maternal mothers. Methods: A case-control study was conducted on the maternal mothers at Kertha Usada Singaraja Bali Hospital, with 106 cases and 106 controls, using maternity medical records data in January-December 2016. The cases and controls were adjusted to the parity. The data were collected using questionnaires consisting of 2 parts: the first part was about the demographic characteristics, and the second part was about the time of membrane rupture and hemoglobin level at the delivery. The obtained data were analysed using descriptive and analytic statistics on the computer program. Result: On univariable analysis, the prevalence of PROM equalled to 28,3% in maternal anemia group. In bivariate analysis, the risk factors of were anemia status, maternal activity, and maternal age (p <0.05). A multivariable analysis of conditional logistic regression analysis, controlling the possibility of confounding factors, showed that pregnant women with anemia would be at risk of PROM 3.59 times greater than non-anemic mothers (OR = 3.59, 95% CI = 1.82-7, 09). Conclusion: The risk of PROM is higher in anemic maternal mothers than in non-anemic mothers, after homogenising with parity variables.